The impacts of the Covid-19 pandemic on the hedging effectiveness of Malaysian crude palm oil futures - Lee, Qin Yu (2022)
This paper examines the hedging effectiveness of Malaysian Crude Palm Oil Futures (FCPO). During the current outbreak of Coronavirus (Covid-19) disease, the growth of the crude palm oil (CPO) market would rely on the effectiveness of FCPO in mitigating the intensified price volatily. Thus, establishing the optimal hedge ratio is crucial for devising an effective hedging strategy. This paper utilises the Malaysian CPO spot and futures prices, on a daily frequency from 1st August 2016 to 9th August 2021. To stress on the Covid-19 pandemic, the two data sets are spilt into two sub-periods comprised of the pre-Covid period beginning 1st August 2016 to 15th March 2020 and the Covid period beginning 16th March 2020 to 9th August 2021. Both constant and dynamic models, in particular the OLS, B-VAR, B-VEC, DVEC M-GARCH, and BEKK M-GARCH models, are employed in estimating the optimal hedge ratios. Results revealed that the FCPO was an effective instrument in minimising risk during the Covid period, as a higher percentage of risk reduction was realised in its underlying cash position regardless of the methods employed during Covid than the pre-Covid period. On the other hand, the negative risk reduction percentages accompanying all models during the pre-Covid period proved that the FCPO was not only ineffective at hedging the systematic risk in the CPO cash market, but it had also increased the price risk of the spot portfolio. The empirical results also observed that the dynamic bivariate GARCH models employed in the study, notably the BEKK M-GARCH model, outperformed all the other models applied, as its MVHRs provided the greatest Sharpe (reward-to-variability) ratios in all periods defined in the study. This outcome is consistent with the findings of Yang and Allen (2004), Kumar et al. (2008), Choudhry (2004), and Park and Switzer (1995), to mention but a few. Overall, the paper’s analyses and findings suggest that the efficiency of FCPO could be improved by enhancing market liquidity through the execution of trading programmes which readily offer trading knowledge to traders, as well as lowering transaction costs.